Physical Activity in Hospice Care: A Social Ecological Perspective to Inform Policy and Practice. Issue 3 (2nd July 2020) - Burke, Shaunna; Utley, Andrea; Belchamber, Caroline; McDowall, Louise
ABSTRACT: Purpose : Physical activity (PA) is increasingly being used in hospice care as a rehabilitation strategy to help patients manage symptoms and improve quality of life. However, little is known about how to design and deliver interventions that promote uptake and maintenance of PA in this population. Single-level approaches (i.e., psychological models) have primarily been used to study factors that influence PA engagement among patients with advanced, incurable disease and therefore offer a limited perspective on strategies that target changes beyond the individual level. This study explored perspectives on factors perceived important for influencing PA participation in hospice care using a social-ecological framework. Method : Patients (n = 27) and health providers (n = 5) from multiple hospices (n = 5) across the UK were involved in this study. Data were collected using focus group and individual semi-structured interviews and analyzed using a thematic framework approach. Results : Eight main themes were perceived to be important for influencing PA engagement at the individual, interpersonal, physical environment, community, and policy levels including: (1) PA as therapy; (2) apprehension about PA-induced harm; (3) group-based PA with peers; (4) supervised PA sessions; (5) limited facilities and access; (6) patient-centered approach; (7) lack of a strong PA culture and; (8) absence of a policy and guidance for PA provision. Conclusion : Hospice-based PA interventions that target multiple levels simultaneously may be more effective at successfully changing and sustaining patients' PA behavior. Study findings provide evidence-based recommendations that may facilitate the effective delivery of PA interventions in hospice care.